The Misunderstood Role of Foreign Language Departments as Integrators of Knowledge Across Disciplines - Wiwczaroski, Troy B. (Acta Agraria Debreceniensis, 2002)
Special purpose language courses have always pushed the boundaries that set them apart from, for instance, courses offered in a business department. When we as foreign language teachers enter the special purpose language classroom and begin to explore such areas as ecology, agriculture, biology, mathematics or even law, we inevitably have had to immerse ourselves in those disciplines, in order to be effective. Foreign language departments, like those from any other field of academia, are continually developing courses with cross-disciplinary topics which challenge the competence of our staffs. However, my experience tells me that our ability as language teachers to integrate knowledge from across the disciplinary spectrum is misunderstood, mistrusted and under-exploited. This article explores this unused, and sometimes undiscovered, potential.